Leveraging project insights to strengthen WEAI for climate research - Koxha, Leona; O’Connor, Eileen; Alvi, Muzna; Chadha, Deepali; Ewell, Hanna; Gartaula, Hom Nath; Ketema, Dessalegn; Lutomia, Cosmas; Mukhopadhyay, Prama; Nchanji, Eileen; Puskur, Ranjitha; Rietveld, Anne M.; et al. (International Food Policy Research Institute, 2025)
Key messages • Measuring women’s empowerment in the context of climate change, resilience, and adaptation requires a flexible climate module—not a rigid, universal set of indicators. • Collective agency, community involvement, and social networks are critical to climate resilience. The project-level Women’s Empowerment in Agriculture Index (pro-WEAI) should expand its climate module to better capture these community dynamics and collective actions. • Integrating qualitative methods strengthens pro-WEAI’s effectiveness and ensures the tool is tailored to local contexts, which is essential for collecting meaningful and holistic data.